Pembelajaran I–SETS (Islamic, Science, Environment, Technology and Society) terhadap Hasil Belajar Siswa - Rita Rahmaniati; Supramono Supramono (​Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2015)
The purpose of this research is to measure the effect of study of I-SETS (Islamic, Science, Environment, Technology and Society) toward the student’s study result in experiment group. The research method is using quantitative approach with quasi experiment and construction of Nonrandomized Control Group Pretest-Postest Design. The population in this research is X grade student from MA Darul Ulum Palangka Raya academic years 2012/2013, sample in this research is X-A grade student (experiment group) and X-B grade student (control group). The result of this research showed that: (a) Student’s result in experiment group was increasing from the pre-test to the post-test with the average from 46,29 becomes 71,41, whereas N-gain has an average 0,47 (b) Student’s result in control group from the pre-test to the post-test with the average from 43,90 becomes 63,53, whereas N-gain has an average 0,36. (c) Hypothesis examination of one way anova showed that study of I-SETS has an effect to the student’s result in experiment group. In this matter we can see based on the table of anova with the significant score = 0,003 more small than 0,05 (0,003 < 0,05) so Ho is denied dan Ha is accepted.